Effect of spray-drying conditions on the physical and antioxidant properties of a hydrolysate from red tilapia (Oreochromis spp.) viscera (2023)
ABSTRACT: Fish hydrolysates have become one of the most remarkable sources of bioactive peptides. However, the processing conditions for incorporating hydrolysates into food matrices can affect their bioactive performance. The effect of temperature and pH on the radical scavenging activity of tilapia hydrolysate was determined in the wet hydrolysate. Also, a central composite design was used to study the effect of the drying conditions on moisture, drying ratio, productivity, drying rate, and antioxidant activity in the tilapia hydrolysate. The results showed that the hydrolysate has high activity at acidic and neutral pH; but at pH 10, the activity decreases significantly. In the spray-drying process, the antioxidant activity was higher at 115 °C. Moreover, inlet air temperature and feed flow had a statistically significant effect (p < 0.05) on response variables. High inlet air temperature and fast feed flow decrease the moisture of the powder hydrolysate and increase the drying rate and antioxidant activity. Scanning electron microscopy showed liquid bridges between particles with irregular concavities or pores on the surface and the presence of particle agglomerations due to the hygroscopicity of the hydrolysate.